2021
DOI: 10.3390/colloids5040043
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Substrate Temperature on the Evaporative Behaviour and Desiccation Patterns of Foetal Bovine Serum Drops

Abstract: The drying of bio-fluid drops results in the formation of complex patterns, which are morphologically and topographically affected by environmental conditions including temperature. We examine the effect of substrate temperatures between 20 °C and 40 °C, on the evaporative dynamics and dried deposits of foetal bovine serum (FBS) drops. The deposits consist of four zones: a peripheral protein ring, a zone of protein structures, a protein gel, and a central crystalline zone. We investigate the link between the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
(96 reference statements)
1
7
0
Order By: Relevance
“…Furthermore, a few recent studies examined the formation of these protein-saline drying drops at different elevated substrate temperatures. The findings of these experiments confirmed that the final morphological patterns are mainly dependent on the environmental conditions (higher vs. lower drying rate) [24][25][26].…”
Section: Introductionsupporting
confidence: 71%
“…Furthermore, a few recent studies examined the formation of these protein-saline drying drops at different elevated substrate temperatures. The findings of these experiments confirmed that the final morphological patterns are mainly dependent on the environmental conditions (higher vs. lower drying rate) [24][25][26].…”
Section: Introductionsupporting
confidence: 71%
“…Figure 1 (a -b) shows an example of the patterns formed by a dried drop of CSF from a healthy patient. In the formation of these patterns, various hydrodynamic and physicochemical processes occur that depend on various conditions, such as temperature and humidity, resulting in complex fractal-like patterns [16].…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of patterns in deposits is a frequent phenomenon that emerges in drying droplets with nonvolatile species [ 19 , 20 , 21 , 22 ]. The literature reveals that the coffee ring can appear in both simple and complex droplet systems [ 23 , 24 , 25 , 26 ]. The “coffee-ring effect” is a ring-like shape pattern observed in the evaporation of droplets containing suspensions [ 27 ], large colloids, nanoparticles [ 28 ], or individual molecules [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, at low RH, the ions attach at random positions, resulting in amorphous crystal structures. The substrate temperature can strongly affect the modes of drying and the final pattern of colloidal and protein drops [ 24 , 52 , 53 , 54 ]. Indeed, the interesting pattern called “eye-like pattern”, a large aggregate enclosed in a uniform coating, results from a conformational change from native to irreversible folding of proteins induced by a hot substrate [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation